Descriptive study of the epidemiological profile of deaths by suicide in the state of Roraima, Brazil, from 2014 to 2017 - Macedo, João Pedro Soares de; Cardoso, Thalia Inácia Araújo (ABCS Health Sciences, 2020)
Introduction: Suicide is one of the top three reasons of death worldwide for the 15- to 44-year age range. The Brazilian state of Roraima has shown indicators that draw attention when compared to national rates of suicide. In this sense, for the proposal of preventive measures appropriate to the state’s reality, it is important to understand the local epidemiological particularities. Objective: to identify the epidemiological profile of deaths by suicide in the state of Roraima, Brazil, between 2014 and 2017. Methods: Descriptive, population-based documentary research. The source of information was the database from the Brazilian public health system (DATASUS). The analysis included deaths by residence caused by suicide from 2014 to 2017. Cut-outs were established according to the variables incidence by municipality, marital status, age, gender, color/race, place of occurrence and method of suicide. Results: 176 deaths were reported in the state of Roraima during the period studied. The average mortality coefficient was 8,6/100.000 inhabitants. Deaths were more frequent among men (73.9%), aged 20 to 29 years (31.2%), resident in the state capital (52.8%), brown (64.2%) or indigenous (25.6%) and single (69.9%). The main suicide method was hanging, strangulation and suffocation (87.5%), with the domicile being the most usual place (72.1%). Conclusion: The results imply the need to act on the problem, which grows in proportion and gains prominence in the national indicators. Suspicion of suicidal behavior in the face of consolidated data may reduce the incidence.